DESCRIPTION OF EARLY DETECTION AND PREVENTION OF HYPERTENSION IN BLANG MONLUNG VILLAGE IN THE WORKING AREA OF LHOK KRUET HEALTH CENTER - Lensoni , Lensoni; Hidayah, Hidayah (Transpublika Publisher, 2024)
Hypertensive disease is one of the significant health problems, both in the world and in Indonesia. Hypertension, often referred to as the